“Saya Mau Bu!” or “Aku Mau Bu!”? from the Teachers and Students’ Point of View - Ienneke Indra Dewi (Lingua Cultura, 2009)
Article describes a research which purpose was to find out whether there was a shift in the use of “aku” and “saya” from the children and teenagers’ points of view as well as their teachers’s. The shift of those expressions was based on the factors of concept, family education,, and the influence of media i.e. television. The objects of this research were 140 elementary and high school students as well as their teachers. Questionnaires were distributed to them. The results showed that there was a shift from the expression “saya” to “aku” in the students and teachers’ perception. However, when tested using statistics, the differences in the shift and in the perception between students and teachers concerning this matter were not significant.